The Effect of Service Quality on Customer Satisfaction at PT. PLN (Persero) in Makassar City - Tunggul Prasodjo (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
This study aims to determine the service quality of PT. PLN (Persero) in Makassar City. This type of research is quantitative. Data collection techniques were carried out through library research and field research in the form of observations, questionnaires, agency data and documentation. The total population of the study was 24,332 with a sample of 100 people selected at random. The analytical method used is the Simple Linear Regression method. The results showed that the indicators of Service Quality at PT. PLN (Persero) in Makassar City is good because the percentage of Service Quality has high values or a high percentage, especially on the Empathy indicator. Customer Satisfaction in Makassar City is very good because Customer Satisfaction is higher than Service Quality, which means that customers in Makassar City are very satisfied with the service or performance of service providers. Service Quality has an effect on Customer Satisfaction, from the regression model obtained significant results and the percentage value is 66 percent.